Effect of electric and heat shock on morphological characteristics for two varieties of wheat - Hawash , Mohammed M.; Al-Shamma , Laith M.J. (Iraqi Journal of Science, 2022)
Wheat (Triticum aestivum L.) is one of the Poaceae family (Gramineae). Is momentous for human nutrition, and the stresses can affect strongly on the phenotype characteristics of the plant. The aim of this study was to determine how electric shock on germinated grain (for 2.5, 5, and 7.5 mins.) and heat shock at ( 35 oC, 40 oC and 45 oC) applied after phase out the radical length of 2-5 mm, from the grain of two wheat Varieties: “Baghdad 1” and “Babylon 113”. The electric shock for 2.5 mins., lead to delay of flowering, from day to 50 % flowering was 93 day, as well as, gave lowest value of plant height 64.5cm and lowest spike length was 10.7 cm. While The highest flag leaf area was obtained by electric shock for 5 mins. was 56.6 cm2 compared to control treatment which was 28.9 cm2. The effects of heat shock at 45 oC, gave maximum plant heights was 78.3 cm and highest spike length was 15.3 cm. In response to electric and heat stress in both varieties, clear differences were observed. Baghdad 1 variety gave the minimum days from sowing date to 50% flowering was 84.85 day and maximum plant height rate 73 cm, while highest rate of flag leaf area 48.1 cm2 and highest spike length was 13.8 cm, by Babylon 113 variety. There is significant interaction between varieties and treatments, Babylon 113 for Es 5 minutes, gave highest value of flag leaf area was 65.8 cm2, and highest spike length 16.7 cm,. Whereas Babylon 113 for Es 2.5 minutes, gave maximum days to 50% flowering which was 93 day, lowest value of plant height 60.5 cm, and lowest spike length 10 cm.